Facile conversion of ammonia to a nitride in a rhenium system that cleaves dinitrogen. Issue 14 (4th March 2022) - Connor, Gannon P.; Delony, Daniel; Weber, Jeremy E.; Mercado, Brandon Q.; Curley, Julia B.; Schneider, Sven; Mayer, James M.; Holland, Patrick L.
Abstract : Rhenium–PNP complexes split N2 to nitrides, but the nitrides do not give ammonia. Here, the thermodynamics of the hypothetical N–H bond forming steps are evaluated through the reverse reaction, showing that the first H addition is the bottleneck. Abstract : Rhenium complexes with aliphatic PNP pincer ligands have been shown to be capable of reductive N2 splitting to nitride complexes. However, the conversion of the resulting nitride to ammonia has not been observed. Here, the thermodynamics and mechanism of the hypothetical N–H bond forming steps are evaluated through the reverse reaction, conversion of ammonia to the nitride complex. Depending on the conditions, treatment of a rhenium(iii ) precursor with ammonia gives either a bis(amine) complex [(PNP)Re(NH2 )2 Cl] +, or results in dehydrohalogenation to the rhenium(iii ) amido complex, (PNP)Re(NH2 )Cl. The N–H hydrogen atoms in this amido complex can be abstracted by PCET reagents which implies that they are quite weak. Calorimetric measurements show that the average bond dissociation enthalpy of the two amido N–H bonds is 57 kcal mol −1, while DFT computations indicate a substantially weaker N–H bond of the putative rhenium(iv )-imide intermediate (BDE = 38 kcal mol −1 ). Our analysis demonstrates that addition of the first H atom to the nitride complex is a thermochemical bottleneck for NH3 generation.